A Transitivity Analysis of Putin’s ideological stance in the “Financial Times” Online Newspaper in 2019 - Novrian Syaputra Motumona; Suswanto Ismadi Megah (CAHAYA PENDIDIKAN, 2022)
This study aims to unmask ideological stances of Vladimir Putin by using transitivity analysis. The dataset obtained from the transcription of Vladimir Putin Interview in the Financial Times newspaper in 2019. By adopting Transitivity analysis of Halliday and Matthiessen’s theory (2014) enable to uncover ideological stances of Putin based on lexicogrammar in the transitivity system of the process types. The findings show that the highest frequency of the Transitivity process used by Putin’s interview using the Material process , the Mental and the Verbal process.  This process presents that Putin has inclined to present that his the real hard work president as the Material process as process of doing, then he used the Mental process to touch the reader’s heart to sympathy to him. While the Verbal process is used to  say out in his interview, since the process of Saying is to display that Putin wants to show that he has an authority and has great power to influence the readers and the people of Russia. This is done by Putin to attract the readers to follow at least support his way to run his country.